Report of the Working Group on Shipbuilding and Shiprepair Industry for the Tenth Five Year Plan - Planning Commission (Planning Commission, 2001)
This summary is divided into two parts. Part-I covers the first four terms of reference of the Working Group viz. review of achievement and contribution, review of role and relevance of ship building and ship repair industry, policy measures to promote ship building and ship repair and possibility of conversion of shipyards to joint ventures, covers the remaining four terms of reference of the Working Group viz. evaluation of productivity and economics of ship building industry, assessment of present employment, assessment of present status of views of IT and suggesting areas of training and development and augmentation of the present institutional infrastructures.
Government of India, Planning Commission